The Importance of Nutrition, Immunization, and Stimulation of the First 1000 Days of Life in Toddlers in Barugbug Village, Jatisari, Karawang - Hidayat, Rachmat; Wulandari, Patricia (Indonesian Community Empowerment Journal, 2022)
Nutrition and health problems are problems in Indonesia. These nutritional and health problems will affect the health of infants and toddlers. This community service program is expected to increase public knowledge and insight regarding the importance of nutrition, immunization, and stimulation in the first 1000 days of life, reduce malnutrition rates in toddlers and fulfill health facilities and infrastructure in Barugbug Village. The community service program was carried out for 5 months. The series of activities carried out in this program include counseling, mobile integrated services post (posyandu), pre-development screening questionnaire (KPSP), nutrition consultation, the direct practice of child stimulation, advocacy, and training of trainees (TOT). The results of the implementation of this program are an increase in public knowledge. A reduction in under-nutrition in children under five can be measured by conducting mobile Posyandu and monitoring nutritional status, increasing the intelligence of multiple children by conducting the pre-screening development questionnaire (KPSP), and practicing directly stimulating children, improving health status through nutrition consultations.